Penggunaan Model Pembelajaran Kooperatif Tipe Teams Games Tounament (TGT) untuk Meningkatkan Kerjasama Siswa Kelas V SDN Kleco 1 Surakarta - Putri, Nur Amalia; Sayekti, Ika Candra; Tasmun, Tasmun (FONDATIA, 2024)
This research is motivated by student cooperation that has not appeared during the learning process in fifth grade students of SD Negri Kleco 1 Surakarta. This study aims to describe the application of the TGT type cooperative learning model to improve the cooperation of fifth grade students of SD Negri Kleco 1 Surakarta. the research method used is class action research (PTK). The research subjects were fifth grade students of SD Negri Kleco 1 Surakarta, totaling 20 students. The data collection techniques used were observation and questionnaire. Data analysis used quantitative analysis of data from pre-cycle results, cycle I and cycle II. The results showed that in pre-cycle observations with an average of 2.0 included sufficient criteria, in cycle I an average value of 2.6 included good criteria and cycle II an average value of 3.3 included very good criteria. And in the results of the questionnaire the level of student cooperation in the pre-cycle, the average student cooperation was 62.4%, included sufficient criteria, increased by 11.6% in cycle I to 74% included good criteria and cycle II increased by 8.8% to 82.8% included very good criteria. The increase in student cooperation from pre-cycle, cycle I and cycle II shows the success of student cooperation when using the TGT learning model, so the use of the TGT type cooperative learning model can improve student cooperation.